Development of a Landmark Land Use and Management Framework for Liberia - Ellen Pratt (African Journal on Land Policy and Geospatial Sciences, 2020)
In October 2016 the Liberia Land Authority (LLA|) was legislated as the Nation’s first one-stop-shop for land management and administration. The LLA has the statutory mandate to administer land administration across the nation. The Authority is charged with supporting the development of a National Land Use and Management Agenda. This process commenced with the development of a National Land Use and Management Framework, especially poignant with the passage of Liberia’s landmark Land Rights Legislation, which advocates for the development of land management plans for all customary communities nationwide.